Innovation in Family Firms: Examining the Inventory and Mapping the Path - Filser, Matthias; Brem, Alexander; Gast, Johanna; Kraus, Sascha; Calabro, Andrea (International Journal of Innovation Management, 2016)
Over the past decade, research on innovation in family firms has received growing attention by scholars and practitioners around the globe with a wide range of aspects explored within the current body of literature. Despite the constantly growing number of scientific publications, research lacks a comprehensive and critical review of past and present research achievements. First, conducting a bibliometric analysis with a focus on innovation in family firms, we identify five topical clusters that help to understand the foundations of recent findings: namely ownership and governance, structural settings, organizational culture and behaviour, resources, and innovation and strategy. Second, based on a thorough literature review the major research avenues are reflected. The comparison of the results of both analyses showed the following areas for future research on family firm innovation: members‘ individual human capital and their leadership behaviour, openness to externals, cross-country comparisons, and finally the family‘s functional integrity on innovation performance.